МЕХАТРОНННЫЕ СИСТЕМЫ ГЕНЕРИРОВАНИЯ ЭЛЕКТРОЭНЕРГИИ НА ОСНОВЕ ЭЛЕКТРИЧЕСКИХ МАШИН С САМОВОЗБУЖДЕНИЕМ - Гарганеев , А.Г.; Харитонов , С.А. (Інститут електродинаміки НАН України, Київ, 2013)
Principles of electric power generation by power supply systems based on self-excited electrical machines are presented in this paper. Functioning conditions of aircraft power supply systems were analyzed. Advantages and disadvantages of permanent magnet synchronous generators were revealed. Similarity of self-exciting processes in DC electrical machines – induction and hysteresis synchronous ones – is revealed. Block diagrams that show similarity of self-exciting processes in DC generator – induction and hysteresis synchronous ones – from the automatic control theory point of view are provided. It is shown that the controlled generation systems contained semiconductor converters are possible to be constructed. References 8, figures 2.